Agriculture, food security, and nutrition: a causal mediation analysis of a multi-sectoral intervention. - Cunningham, Kenda. (Tufts University. Tisch Library., 2020)
This presentation details a causal mediation analysis of a multisectoral intervention on agriculture, food security, and nutrition in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy